Time of Fusarium inoculation and post-anthesis temperature stress affect FHB severity and DON concentration in winter wheat - Okereke, Victor; Jones, Hannah; Gooding, Mike (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Two pot experiments were conducted using elite lines and near isogenic lines (NILs) of winter wheat in a controlled environment to evaluate the effect of time of inoculation and subsequent increase in temperature during grain-filling on Fusarium head blight (FHB) and deoxynivalenol (DON) on the infected wheat grains. The experiments were a complete factorial combination with randomised replicates. Fusarium graminearum was used to spray inoculate wheat spikes at glume loose (GL). GL was established when the lower glume could be opened with a thumbnail. Fusarium inoculation was done at glume loose (GL+0), 4 and 8 days after (GL+4 and GL+8), respectively. Pots transferred to controlled environment cabinets set at 23/15oC or 28/20oC. Results reveal that FHB severity showed a significant (P<0.05) cultivar and temperature interaction in both elite and near isogenic lines. High temperature increased FHB severity by 35% in the NILs. DON concentration showed cultivar sensitive in both sets of cultivars. Inoculation at GL+4 which corresponded with the mid-anthesis gave the highest FHB severity and DON concentration in NILs, while the elite cultivars showed cultivar sensitive to DON accumulation regardless of the time of Fusarium inoculation.